Renal Angiomyolipoma Associated with Inferior Vena Cava Thrombus. (16th December 2009) - Durand, Xavier; Renard-Penna, Raphaelle; Comperat, Eva; Bitker, Marc-Olivier; Richard, Francois
Abstract : A 57-year-old woman was found to have an inferior vena cava involvement of a known sinusal angiomyolipoma incompletely resected three years beforehand. Intravascular extension into the IVC of angiomyolipoma has rarely been reported. We present a new case and reconsider the literature about this uncommon complication of a benign renal tumor.